Application of the Talking Stick Cooperative Learning Model in Improving Student Learning Outcomes - Hendra Saputra S. Adiko; Monalisa Djafar (Newinera Publisher, 2022)
The purpose of this study was to improve student learning outcomes through the application of the talking stick cooperative learning model in social studies class IV at SDN 11 Limboto Barat. This type of research is Classroom Action Research. In the initial observation, there were 15 students who completed 54%. After the first cycle of action was carried out, it increased to 21 students who completed 75%, who had not completed 7 students or 25%. The implementation of the second cycle that was completed increased by 26 students, 93% and those who had not completed 2 students or 7%. Based on the results of the research conducted, it can be concluded that the talking stick cooperative learning model can improve student learning outcomes in social studies learning in class IV SDN 11 Limboto Barat.